Participatory Online News Expertise and Credibility: A Study on Visual Citizen in TikTok bikini.bottom.news - Amelia, Syfa; Wibowo, Arif Ardy (Universitas Gadjah Mada, 2024)
TikTok already has the power to spread news apart from providing entertainment content. The emergence of TikTok is very massive and is used by many groups. TikTok brings a novelty with its content which is not only entertaining like lots of challenge videos and also often informative because many news channels have started to use TikTok as their media platform. One of them is the Bikini Bottom News TikTok account which actively reports the latest information on both socio-political issues and issues of international celebrities. The expertise of journalists and the credibility of TikTok, which started as an entertainment platform, come into question when we talk about news. This study analyzes the expertise and credibility of participatory online news in the visual community or citizens. Using case studies by conducting literature reviews and discussions with informants who have the same background, namely students regarding the bikini.bottom.news account, the authors obtain data that the TikTok platform, especially on the bikini.bottom.news account has two acceptances, which are considered to have met the skill requirements of a journalist to be trusted for the credibility of the news content and are considered not in accordance with the provisions of the expertise of a journalist and the content is considered not credible.